Antioxidant and Cytotoxic Evaluation of Garcinia dioica Blume Stem Bark Extracts - Vivi Anggia., M.Farm; Hendri Aldrat; Arsha Waniza Rusdi (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
Garcinia dioica Blume, locally known as asam kandis, is a member of the Garcinia genus, which is recognized as an important source of xanthones, a class of polyphenolic compounds associated with diverse biological activities. Previous studies have demonstrated that xanthones possess antioxidant, anti-inflammatory, antimicrobial, and cytotoxic properties. The present study aimed to evaluate the antioxidant and cytotoxic activities of G. dioica stem bark extracts. The antioxidant analyzes with DPPH method and the cytotoxic activities with BSLT method. Asam kandis stems were extracted in stages with hexane, ethyl acetate, and ethanol. All extracts exhibited very strong antioxidant activity compared to vitamin C, with an IC50 of 3.86. The 96% ethanol extract showed the highest activity (IC₅₀ 10.59 ppm; AAI 1.89), followed by n-hexane and ethyl acetate extracts with IC50 of 12.96 and 20.04 ppm. The cytotoxic activity of ethyl acetate was proven to provide significant results, followed by ethanol and hexane extracts with LC50 of 30.50 ppm, 37.68 ppm, and 59.10 ppm, respectively. These results indicate that the bark of Garcinia dioica exhibits significant antioxidant and cytotoxic activity, suggesting its potential for further research as a source of anticancer compounds.